2012
DOI: 10.5194/se-3-1-2012
|View full text |Cite
|
Sign up to set email alerts
|

Bio-chemostratigraphy of the Barremian-Aptian shallow-water carbonates of the southern Apennines (Italy): pinpointing the OAE1a in a Tethyan carbonate platform

Abstract: Abstract. Low biostratigraphic resolution and lack of chronostratigraphic calibration hinder precise correlations between platform carbonates and coeval deep-water successions. These are the main obstacle when studying the record of Mesozoic oceanic anoxic events in carbonate platforms. In this paper carbon and strontium isotope stratigraphy are used to produce the first chronostratigraphic calibration of the Barremian-Aptian biostratigraphy of the Apenninic carbonate platform of southern Italy. According to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…The carbon-isotope data from Monte Raggeto is taken from Di Lucia et al (2012) and the stratigraphic position of the OAE 1a record follows Amodio et al (2013Amodio et al ( , 2003, D'Argenio et al (2011D'Argenio et al ( , 43 2004), Di Lucia et al (2012) and Wissler et al (2004), based on carbon-isotope, sequence, magneto-and cyclostratigraphic investigations. Carbon isotopes of the Coppitella section are taken from Luciani et al (2001), who identified the record of OAE 1a by integrated bio-and carbon-isotope stratigraphy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The carbon-isotope data from Monte Raggeto is taken from Di Lucia et al (2012) and the stratigraphic position of the OAE 1a record follows Amodio et al (2013Amodio et al ( , 2003, D'Argenio et al (2011D'Argenio et al ( , 43 2004), Di Lucia et al (2012) and Wissler et al (2004), based on carbon-isotope, sequence, magneto-and cyclostratigraphic investigations. Carbon isotopes of the Coppitella section are taken from Luciani et al (2001), who identified the record of OAE 1a by integrated bio-and carbon-isotope stratigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…The Coppitella section has been analysed by Luciani et al (2001) for bio-and carbon-isotope stratigraphy identifying the record of OAE 1a. Wissler et al (2004) and Di Lucia et al (2012) studied the Monte Raggeto section and identified the typical carbon-isotope signature of OAE 1a. This interpretation is supported by magneto-, sequence and cyclostratigraphic investigations (Amodio et al, 2013(Amodio et al, , 2003D'Argenio et al, 2011D'Argenio et al, , 2004Wissler et al, 2004).…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…These proxies imply a likely major volcanic phase of the GOJE that introduced CO 2 concentrations 3-6 times higher than before (e.g., Erba and Tremolada, 2004) and added biolimiting and/or toxic metals. The nannoconid crisis and the contemporaneous demise of carbonate platforms suggest that acidifi cation in addition to eutrophication of surface waters contributed to a major biocalcifi cation failure, although low-latitude carbonate platforms were less affected (Di Lucia et al, 2012), perhaps because of the kettle effect in near-tropical settings, compensating the impact of elevated atmospheric CO 2 concentrations (Skelton and Gili, 2012).…”
Section: Direct and Indirect Consequences Of Lip Volcanism On Ecosystmentioning
confidence: 99%